Biosynthèse de nanoparticules à base d’extrait de plante (Myrtus communis) et la caractérisation de leurs activités biologiques - Belahouel, Khaled (My University, 2021)
The green biosynthesis of nanoparticles is developing more and more rapidly and almost universally, and this phenomenon is particularly marked for silver and copper nanoparticles responsible for protecting foodstuffs, and their use as a powerful antibacterial agent. The objective of this work is the characterization of nanoparticles of silver, copper and bio zinc synthesized from extracts of the medicinal plant Myrtus communis. The present study has demonstrated the antibacterial activity of nanoparticles synthesized from this plant, especially copper and silver NPS which have shown significant antibacterial activity against Staphylococcus aureus.
Keywords: Myrtus communi. ; Nanoparticules ; Composés phénoliques; Biosynthèse; Activité antibactérienne.